The existence of the Miyazaki-Wilson-Spence equilibrium with continuous type distributions - Irina Gemmo; Christian Kubitza; Casey G. Rothschild (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2018)
We prove the existence of an equilibrium in competitive markets with adverse selection in the sense of Miyazaki (1977), Wilson (1977), and Spence (1978) when the distribution of unobservable risk types is continuous. Our proof leverages the finite-type proof in Spence (1978) and a limiting argument akin to Hellwig (2007)'s study of optimal taxation.
Keywords: D82; G22; D41; 330; asymmetric and private information; insurance market; adverse selection; equilibrium